Controllable ultrahigh-affinity molecular recognition - Fang-Yuan Chen; Han-Fang Zhang; Kang Cai; Dong-Sheng Guo (Supramolecular Materials)
High-affinity molecular recognition plays a crucial role in both biological and artificial host-guest systems, ensuring robustness in complex environments or at extremely low concentrations. Achieving exceptionally high binding affinity in artificial receptors remains a fundamental challenge for supramolecular chemistry. However, while ultrahigh binding affinity is desirable for stability, it may limit the dynamic behavior of host-guest systems, thereby restricting potential applications. Hence, controllable ultrahigh-affinity molecular recognition (CUAMR) systems allow guest release in response to precise stimuli (such as photo, pH and redox), which hold significant promise across diverse fields. This paper focuses on the introduction of CUAMR and functional applications of such controllable systems, highlighting current challenges and future prospects.